2018
DOI: 10.1259/bjr.20170931
|View full text |Cite
|
Sign up to set email alerts
|

Technical challenges of imaging & image-guided interventions in obese patients

Abstract: Obese patients challenge imaging departments in their ability to obtain diagnostic quality images and to perform image-guided interventions. These technical challenges include properly accommodating large patients on imaging equipment, adjusting equipment settings to address imaging limitations, and pre-planning and preparation for image-guided interventions to insure safe and successful outcomes. Knowing and addressing these challenges can result in successfully addressing the imaging and image-guided interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 28 publications
0
68
0
2
Order By: Relevance
“…However, perhaps a more pressing concern is that highlighted in the recent editorial in Obesity, namely, that appropriate resources for those with (severe) obesity are often inadequate in hospitals 7 ; for example, the access to imaging may be limited by the lack of machines able to accommodate patients with severe obesity 8 . If the more complex lifting and handling demands of those with obesity 9 are also factored in, there is a real risk that people with severe obesity may be seriously disadvantaged regarding health care.…”
mentioning
confidence: 99%
“…However, perhaps a more pressing concern is that highlighted in the recent editorial in Obesity, namely, that appropriate resources for those with (severe) obesity are often inadequate in hospitals 7 ; for example, the access to imaging may be limited by the lack of machines able to accommodate patients with severe obesity 8 . If the more complex lifting and handling demands of those with obesity 9 are also factored in, there is a real risk that people with severe obesity may be seriously disadvantaged regarding health care.…”
mentioning
confidence: 99%
“…Although radiological imaging is a widely available, as well as affordable method, due to the dangers of ionizing radiation from CT and X-ray equipment, it is not suitable for frequent use, and there are other contraindications to this procedure. It is necessary to consider imaging pregnant women, other complications can be caused by the presence of metal objects, the inability of the patient to take a deep full breath or also to adapt the equipment for too thin or obese patients (Uppot 2018).…”
Section: Limitations Of the Used Methodologymentioning
confidence: 99%
“…A patient's weight, abdominal girth, and distribution of fatty tissue must be taken into account when assessing whether a particular scanner or other type of imaging equipment can accommodate that patient. [6][7][8] Our analysis revealed that there are facilities in Pennsylvania that are not able to accommodate some patients due to their large size or weight. Reviewing the event details drew our attention to the fact that some patients were brought to an imaging department for a study without first being measured or with only their weight being measured.…”
Section: Imagingmentioning
confidence: 99%